WHAT STRONTIUM ISOTOPES TEACH US ABOUT GROUNDWATER. - Quaggio, Carolina Stager [UNESP]; Gastmans, Didier [UNESP]; de Souza Martins, Veridiana Teixeira (Derbyana, 2021)
The ratio between the strontium isotopes (87Sr/86Sr) is an excellent hydrogeochemical tracer. Thanks to its conservative characteristic, which means that no fractionation will take place in face of geological superficial processes, for example, water-rock interaction, weathering, salinization processes and in the determination of 87Sr sources, strontium isotopes constitute relevant information to understand groundwater circulation. In Brazil, there are few hydrogeological studies that use strontium isotopes to assess hydrogeochemical processes. The little use of this versatile technique is explained by the restricted number of laboratories in Brazil with analytical capacity to determine 87Sr/86Sr ratios in groundwater, since high-resolution equipment – such as thermal ionization (TIMS) and inductively coupled plasma (ICP-MS) mass spectrometers –, specialized teams and infrastructure are required. Furthermore, there is the complexity of the interpretation of the results, which requires complementary data and deep knowledge of the hydrogeological context. In this sense, this paper aims to motivate the use of strontium isotopes by presenting the key concepts to comprehend and determine strontium isotopes in groundwater, starting with the review of the theoretical concepts of the strontium geochemistry, strontium isotopy and the strontium isotope cycle. Sampling and analytical procedures are presented, followed by a review of groundwater studies that have applied this tracer in Brazil. Final considerations and the presentation of opportunities to apply the strontium isotope technique to hydrogeological studies are made. Since 87Sr/86Sr data are lacking for the majority of the Brazilian aquifer systems, the opportunity exists to expand this line of research to produce unprecedented data and to include strontium isotopes in groundwater monitoring programs.
O QUE OS ISÓTOPOS DE ESTRÔNCIO NOS ENSINAM SOBRE AS ÁGUAS SUBTERRÂNEAS
Keywords: Aquifers; Brazil; Groundwater; Strontium isotopes